Gluten-free diet among Portuguese coeliac adults: perceived difficulties - Lima,Patrícia (2020)
Introduction: Coeliac disease can cause a great burden in the coeliacs life. Therefore, it is important to assess the difficulties that coeliacs face in their daily life. Objectives: To evaluate the perceived difficulties of self-reported compliance with the gluten-free diet and with out-of-home eating aspects in a convenience sample of Portuguese coeliac adults. Methodology: It was performed a transversal observational study where Portuguese coeliac adults were inquired, filling out an online questionnaire. It comprised three sections: sociodemographic and disease characteristics, self-reported compliance with the gluten-free diet and out-of-home eating aspects. Results: The final sample included 339 participants, where 76.4% were members of Associação Portuguesa de Celíacos, 84.1% were female and the age of coeliac disease diagnosis ranged from 1 to 70 years old. The difficulties identified by the participants in self-reported compliance with the gluten-free diet were Risk of gluten cross-contamination (84.1%), Availability of gluten-free products in public places (coffee shops, hospitals, restaurants, ) (83.8%), Absence of the gluten-free symbol in the products label (52.2%) and the Lack of gluten-free food products offer, at an affordable price (45.7%). In out-of-home eating, the main difficulty was the Lack of information and unconcern of the establishments staff (44.0%). Conclusions: Coeliacs face a lot of challenges in terms of daily food choices. The role of patient support groups and education provided by a follow-up team with professional skills in coeliac disease are vital for its management and long-term outcome.